2008
DOI: 10.1111/j.1751-1097.2008.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

The Length of Esterifying Alcohol Affects the Aggregation Properties of Chlorosomal Bacteriochlorophylls

Abstract: Chlorosomes, the main light-harvesting complexes of green photosynthetic bacteria, contain bacteriochlorophyll (BChl) molecules in the form of self-assembling aggregates. To study the role of esterifying alcohols in BChl aggregation we have prepared a series of bacteriochlorophyllide c (BChlide c) derivatives differing in the length of the esterifying alcohol (C(1), C(4), C(8) and C(12)). Their aggregation behavior was studied both in polar (aqueous buffer) and nonpolar (hexane) environments and the esterifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 50 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…It is well-known that metal complexes of cyclic tetrapyrroles are useful for preparation of functional supramolecules, for example, excitonically delocalized J -aggregates in main light-harvesting antenna systems of green photosynthetic bacteria (called chlorosomes). , Major composite molecules in chlorosomes are bacteriochlorophyll(BChl)s- c / d / e , which have hydroxy and carbonyl groups as well as a coordinative magnesium metal on the y axis (a line through N21 and N23, left drawing in Figure ). These three moieties are essentially required for making chlorosome-like self-aggregates based on coordination bonding (3 1 -O···Mg), hydrogen bonding (3 1 -O−H···OC-13) and strong π−π stacking. Many synthetic studies on clarifying the structural requirements of chlorosomal self-aggregation have been reported, and three types of π-conjugated systems, porphyrin, chlorin, and bacteriochlorin, have been found acceptable for this self-aggregation. We focused on a porphyrin π-system in this report, because the fully conjugated π-system is significantly stable, and the intense Soret band of the aggregated porphyrin situated at around 400−550 nm is well-matched with the sunlight spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that metal complexes of cyclic tetrapyrroles are useful for preparation of functional supramolecules, for example, excitonically delocalized J -aggregates in main light-harvesting antenna systems of green photosynthetic bacteria (called chlorosomes). , Major composite molecules in chlorosomes are bacteriochlorophyll(BChl)s- c / d / e , which have hydroxy and carbonyl groups as well as a coordinative magnesium metal on the y axis (a line through N21 and N23, left drawing in Figure ). These three moieties are essentially required for making chlorosome-like self-aggregates based on coordination bonding (3 1 -O···Mg), hydrogen bonding (3 1 -O−H···OC-13) and strong π−π stacking. Many synthetic studies on clarifying the structural requirements of chlorosomal self-aggregation have been reported, and three types of π-conjugated systems, porphyrin, chlorin, and bacteriochlorin, have been found acceptable for this self-aggregation. We focused on a porphyrin π-system in this report, because the fully conjugated π-system is significantly stable, and the intense Soret band of the aggregated porphyrin situated at around 400−550 nm is well-matched with the sunlight spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The three main scattering peaks of BChl c yielded a unit cell for the aggregate arrangement and the corresponding cell dimensions are compatible with a dimer of BChl c molecules in the asymmetric unit ). Self-assembly experiments with BChl c and BChlide c molecules revealed an important role of the esterifying alcohols, and favor structural models where alcohol tails extend to both sides of the lamellar layer (Klinger et al 2004;Zupcanova et al 2008). Such an arrangement facilitates the hydrophobic interaction between esterifying alcohols from the neighboring layers and provides plausible explanation for the formation of lamellae.…”
Section: Discussionmentioning
confidence: 90%
“…Linear alkyl chains of the semi-synthetic magnesium chlorins also little changed the visible absorption spectra and sizes of their self-aggregates in Triton X-100 micelles, although they would affect deaggregation behaviour by additive 1-hexanol (17). Recently, Zupcanova et al (18) also reported self-assembly of BChl c esterified by several alcohols in aqueous buffer and nonpolar alkanes, where the length of esterifying alcohols affected Q y absorption bands in their visible absorption spectra. Both in vivo and in vitro studies suggested that esterifying alcohols at the 17-propionate had slight influence on BChl organisation in chlorosomal self-aggregates.…”
Section: Introductionmentioning
confidence: 94%